2015
DOI: 10.1016/j.kjms.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the neutrophil–lymphocyte ratio and disease activity in patients with ulcerative colitis

Abstract: Preliminary evidence suggests that a higher neutrophil-lymphocyte ratio (NLR) may be an indicator of active ulcerative colitis (UC). However, it is not clear whether the NLR is a useful and simple indicator of clinical activity in UC after adjusting for the other inflammatory markers. We designed a retrospective study to evaluate the role of the NLR in estimating disease severity in UC patients. The study consisted of 71 patients with UC and 140 age- and sex-matched healthy individuals (control group). The NLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
4
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 29 publications
4
44
4
5
Order By: Relevance
“…NLR at a cutoff value of 2.35 could discriminate between active and a quiescent UC. NLR was elevated compared to inactive UC patients and controls, and a cutoff value of 2.16 indicated the presence of active disease [21][22][23].…”
Section: Discussionmentioning
confidence: 95%
“…NLR at a cutoff value of 2.35 could discriminate between active and a quiescent UC. NLR was elevated compared to inactive UC patients and controls, and a cutoff value of 2.16 indicated the presence of active disease [21][22][23].…”
Section: Discussionmentioning
confidence: 95%
“…In this context, NLR and PLR could be regarded as simple, inexpensive, and effective inflammation markers that have been linked with several inflammatory and neoplastic diseases [8]. Recent studies have shown that NLR and PLR values are strongly associated with the diagnosis and prognosis of ulcerative colitis, tubo-ovarian abscesses, familial Mediterranean fever, brucella arthritis, and colorectal cancer [8,[14][15][16][17][18]. Although PLR changes in HEG patients have not been studied previously, two recent studies demonstrated that NLR levels are increased and correlated in patients with HEG [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…In ulcerative colitis, the extent of neutrophil infiltration correlates with the severity of the disease, and is included in the scoring system of UC severity [11]. Neutrophil-to-lymphocyte ratio (NLR) is increased in the blood of patients with active UC compared to controls [12]. Nevertheless, NLR fails to discriminate between active and non-active UC.…”
Section: Introductionmentioning
confidence: 99%